Mapmonde ou Description Generale du Globe Terrestre - Chatelain, Henri Abraham, 1664-1743 (F. l'Honore & Chatelain, 1703)
18th century Copper engraving handcolored with watercolor. Outline color. Relief shown pictorially. Printed at top across center: "Mapmonde ou Description Generale du Globe Terrestre." Printed beneath compass rose: "Remarque. Pour parvenir a la connoisance de la Geographie on doit dabord en entendre les principaux Termes. On des range icy dessous par order Alphabetique, et on renvoye le lecteur par un exemple dan le Globe. Ainsi pour faire voir ce que c'est qu'un cap on renvoye au Cap de bonne Esperance; d'un d'etroit on renvoye au detroit-de Gibraltar et ainsi de la plus part des autres termes de la Geographie Voyez. cy dessous." Printed across bottom half in Western hemisphere in Pacific Ocean: "routes faites autour du Monde lan 1616 par Guillaume Schouten, Francois Drac, en 1580, et par Thomas Cavendish, Olivier de Nort, Jacques Mahu, et George Spillemberge quel que annees apres." Printed below equator line on Western hemisphere: "Cercle de l'equateur ou ligne equinoctial qui divise le globe en deux hemispheres la septentrionale et la meridionale passent par le milieu de la zone torride." Printed above the equator line in Western hemisphere: "Zone Torride, est l'espace quil y a du Tropique de Cancer, au Tropique de Capricorne auxdeux costes de La Ligne, qui la coupe en deux parties." Printed in upper right corner next to a drawing of the moon: "La Lune Selon Monsieur Cassini." Printed in upper right corner next to moon: "N. 2" Printed in upper left corner next to a drawing of the sun: "Le Soleil Selon le Pere Kircher." Includes routes and dates of exploration and geographic discovery for several explorers including Sir Francis Drake, Guillaume Schouten, Thomas Cavendish and others. Border contains an ornate vine pattern. Scattered throughout the map are four small drawings of ships. The sun and moon are depicted in upper corners, and a compass rose is shown between the two hemispheres. Included beneath the hemispheres is a table listing continents with countries, capitals and their location on the map. Listed as well are geographical terms for land and sea and their explanations. Of note, California is shown as an island and "Terres Australis Inconnues" is connected to "New Hollande." In China, the Great Wall is visible as are the Himalaya Mountains, although they are not labeled. Prime meridian: l'Isle de Fer. Scale: c.a. 1:60,000,000. Henri Abraham Chatelain (1664-1743) was a geographer and publisher. Most of Chatelain's maps were based on the work of Guillaume Delisle. His most famous work was "Atlas Historique" published in 7 volumes from 1705-1720, 1721 and again 1732-1739. The text of this educative atlas was written by Nicholas Gueudville. Included in this atlas is one of Chatelain's best known, highly-decorative maps, "Carte trés curieuse de la Mer de Sud…," a large foldout map that displays elaborate cartouches and depicts 75 percent of the globe in longitude. Source(s): "Mapmonde, ou, Description Generale du Globe Terrestre." Alaska's Virtual Library and Digital Archives. 2008. Alaska's Virtual Library and Digital Archives. "Mappemonde ou description generale du globe terrestre." National Library of Australia. 2008. National Library of Australia Digital Collections: Maps. Tooley, Ronald Vere. "Tooley's Dictionary of Mapmakers." Hertfordshire: Map Collector Publications Limited, 1979.